Weather services in its - concrete benefits for the society - Eetu, P.; Hautala, R.; Leviakangas, Pekka; Yrjö, P. (2011)
The damages and social costs from weather-related accidents of road transport are significant. Adverse weather conditions such as fog and slipperiness contribute to a significant number of accidents every year. Weather and road weather information services can help to mitigate these harms. In Finland, for example, the socio-economic benefits of current road weather information services for road transport are at least 120 million euro annually in reduced accident and maintenance costs. The benefits come mainly from two sources: traffic information/warning services and winter road maintenance operations. The benefits could be at least doubled by developing more efficient and intelligent information services. Recent technological advances and a predicted increase in extreme weather phenomena are further highlighting the importance of these services. This paper summarises the benefits of weather information services for road transport by reviewing studies conducted in some European countries between the years 2007 and 2010. The value network of weather services is looked at with regard to the different actors and their roles. Potential benefits are also evaluated from the points-of-view of the different actors. Two different aspects of achieved benefits are identified: road network operation and road maintenance. © 2011 by the Intelligent Transportation Society of America.